Dose-Dependent Activation of Putative Oncogene SBSN by BORIS - Gaykalova, Daria (Public Library of Science, 2012)
Testis-specific transcription factor BORIS (Brother of the Regulator of Imprinted Sites), a paralog and proposed functional antagonist of the widely expressed CTCF, is abnormally expressed in multiple tumor types and has been implicated in the epigenetic activation of cancer-testis antigens (CTAs). We have reported previously that suprabasin (SBSN), whose expression is restricted to the epidermis, is epigenetically derepressed in lung cancer. In this work, we establish that SBSN is a novel non-CTA target of BORIS epigenetic regulation. With the use of a doxycycline-inducible BORIS expressing vector, we demonstrate that relative BORIS dosage is critical for SBSN activation. At lower concentrations, BORIS induces demethylation of the SBSN CpG island and disruption and activation of chromatin around the SBSN transcription start site (TSS), resulting in a 35-fold increase in SBSN expression in the H358 human lung cancer cell line. Interestingly, increasing BORIS concentrations leads to a subsequent reduction in SBSN expression via chromatin repression. In a similar manner, increase in BORIS concentrations leads to eventual decrease of cell growth and colony formation. This is the first report demonstrating that different amount of BORIS defines its varied effects on the expression of a target gene via chromatin structure reorganization.